Considering the challenges of the diffusion of innovation in health from the innovator’s perspective: A review and technology spectrum - Ogilvy, Lenore (2016)
The diffusion of innovation is a challenge in all health economies, including the English National Health Service. There is a significant body of research on the diffusion of innovation in health, but there are two lacunae in the literature. First, research has adopted the perspective of implementers and researchers, and excluded the innovator. In order to explore this gap, Greenhalgh, Robert, Bate, Macfarlane and Kyriakidou’s (2004) Conceptual Model for the Diffusion of Innovation in Service Organisations was used as a framework for a re-examination of the literature to focus on insights for innovators. The literature review resulted in the identification of some potentially useful constructs that would support innovators to diffuse their technologies. Preliminary findings were then explored with a panel of experts through a focus group. This expert review revealed some gaps from the innovator’s perspective in Greenhalgh et al.’s (2004) model and as a result, some additional factors for the conceptual model are suggested. Second, there is an inconsistency in the use of the term “technology” and a lack of classification of “health technologies” which would be helpful to innovators – as well as researchers and implementers – in considering how innovation attributes might interact with the adoption, implementation, assimilation and diffusion process. To address this, a “technology spectrum” has been proposed and applied to demonstrate the benefits of developing a classification of health technology.